Socialization of Protection and Insurance Claim Processes for Drivers of Application-Based Companies in Palangka Raya, Indonesia - Wening Mustikaningsih; Nova Riyanti (Indonesian Scientific Publication, 2026)
This research study examines the digital transformation in Indonesia's urban transportation, which has increased the number of online drivers. However, this growth is decoupled from adequate insurance literacy. Adequate comprehension of social security is a prerequisite for professional safety. Initial findings in Palangka Raya indicate a critical baseline literacy score of 15.0, particularly with regard to Jasa Raharja's claim mechanisms. The present study evaluates a participatory educational intervention model with the objective of addressing this knowledge gap. Utilizing a pre-experimental design, the program encompassed ten drivers (N=10) from diverse platforms, including local’s